دور نظام الإنتاج الأنظف في تحقيق مؤشرات التوازن البيئي بدعم من المعرفة البيئية دراسة تحليلية لآراء القيادات الإدارية في عينة من مصانع إنتاج المياه المعدنية في إقليم كوردستان - درويش, رعد الياس; سلطان, حكمت رشيد (Sulaimani Journal for Humanities, 2018)
Paying attention to the environmental issues has increased in the last three decades of the twentieth century, since governments and related parties have realized the industrial revolution’s negative impacts on sustainable development, wasting resources in which future generations have right in it as same as present generations, in addition to increasing environmental phenomena, forming real challenges to the industrial sector in order to keep abreast of the era of globalization and its production and economic effects. To increase the role of this sector in development, ways and means should be found to help the administrative leaders of industrial sector and their employees to think logically and acquire cognitive skills and analysis to the environmental balance and that the acquisition of environmental knowledge may contribute to, and support the path of the relationship between the adoption of the concept of Cleaner Production to achieve environmental Balance in the industrial sector in Kurdistan Region of Iraq. It is hoped that this research contributes to the theoretical and field implementations in clarifying the relationship and impact between cleaner production and environmental balance with support of Environmental Knowledge in Researched Organizations. The research aims at achieving the fundamental objective in diagnosing the role played by the adoption of clean production and environmental knowledge in achieving environmental balance in the researched organizations. The research used a set of statistical techniques to describe and analyze the opinion of (109) of the administrative leaders in (19) water production plant and the data collected by questionnaire form. The paper reached a number of conclusions, the most important of which are: There is a strong correlation and influence between cleaner production and environmental balance, and this relationship is boosted and become stronger with the existence of environmental knowledge, and the paper recommended that organizations should strive to achieve higher degrees of cleaner production requirements and increase knowledge and environmental awareness because of their impact on achieving environmental balance.
Keywords: Cleaner production system; environmental knowledge; environmental balance